AN ANALYSIS OF THE USE OF AMERICAN SLANGS ON EMINEM’S SONG LYRICS - Aryawan Luh Putu Karina Febriyanti (Universitas Pendidikan Ganesha, 2017)
There were two types of speech style which could be divided into formal and informal type. The informal one was well-known by the name of slang. Slang was non-standard language used in the everyday life created by a certain community and usually used by the teenagers in modern era. Slang was not only found in the daily conversation, but also could be found in literary works like song. Song was a literary work which could reflect the reality and express someone’s feelings. This study analyzes the slangs found in five lyrics of Eminem’s song by using descriptive qualitative method. Besides, this study focused on the word formation of the slangs itself. There are 60 data which has been collected from the lyrics. From the analysis conducted, the types of word formation are found in the slangs used in the lyrics, such as blending, clipping, coinage, acronym and onomatopoeia. Mostly, the American slangs in the Eminem’s song lyrics are created by the process of blending and clipping.